Real-life effectiveness and tolerability of the rivastigmine transdermal patch in patients with mild-to-moderate Alzheimer's disease: the EMBRACE study. (23rd May 2013) - Gauthier, Serge; Robillard, Alain; Cohen, Sharon; Black, Sandra; Sampalis, John; Colizza, Diane; de Takacsy, Frederica; Schecter, Robyn
Abstract: Objective: To assess the real-life effectiveness and tolerability of the rivastigmine transdermal patch in patients with mild-to-moderate Alzheimer's disease (AD) in Canada. Research design and methods: Eighteen-month observational, prospective, multi-center, open-label study conducted on AD patients with Standardized Mini-Mental State Examination (SMMSE) score of 10–26 and Global Deterioration Scale (GDS) score of 4–6. Patients were treated with the rivastigmine transdermal patch (Exelon patch* ) 5 cm 2 (4.6 mg/24 hours) or 10 cm 2 (9.5 mg/24 hours), once daily. Main outcome measures: Primary outcome was change in SMMSE from baseline to 18 months. Secondary outcomes included change in SMMSE at 6 and 12 months and change in GDS, Assessment of Patient Ability (APA-C), Overall Patient Assessment Rating (OPAR), caregiver-reported compliance and treatment satisfaction at 6, 12, and 18 months. Results: Among the 1204 patients enrolled, 969 were included in the ITT analysis. Mean (SD) age was 80.2 (8.00) years, disease duration was 0.6 (1.26) years, 62.0% of patients were women, 80.4% were living in the community, and 69.3% were treatment naïve. Mean (SD) baseline SMMSE and GDS scores were 21.8 (3.98) and 4.2 (0.61), respectively. Over 18 months of treatment there were no clinically significant changes in SMMSE and GDS. The majority of patients showed improvement or no change in GDS, APA-C and OPAR over 18 months. The proportion with reported improvement in GDS, APA-C and OPAR was higher than the proportion that deteriorated. Compliance improved from baseline to 18 months and for 88.2% of patients caregivers preferred the transdermal patch to oral medications. Conclusions: The rivastigmine transdermal patch is effective in maintaining cognitive function over 18 months of treatment in patients with mild-to-moderate AD. The safety profile was comparable to the data in the Canadian product monograph. Lack of a comparator group is a potential limitation of the study.